Comparison between Two Transformation Systems for Introducing CMV Coat Protein Construct into Local Hot Peppers - Zainuddin, Z.; Khalid, Norzulaani; Tan, C.S. (Faculty of Science, University of Malaya, 2002)
Two transformation systems, via Agro bacterium tumefaciens and particle bombardment, for two varieties of chilli pepper (Capsicum annuum L.) were determined. The plasmid pCMV.CP was used for the transformation. After transformation, buds were selected on the regeneration medium containing kanamycin (50 mg/l). Based on PCR analysis, transformation via A. tumefaciens was the best approach for introducing a novel chimeric gene into chilli tissues.